The effect of conservation in various cryoprotectants on the properties and morphological structure of the umbilical cord arteries - V. A. Brumberg; T. A. Astrelina; T. F. Malivanova; I. V. Kobzeva; Yu. B. Suchkova; V. A. Nikitina; D. Yu. Usupzhanova; V. A. Brunchukov; S. V. Lishchuk; P. S. Kyzlasov; A. A. Kazhera; V. M. Troyakov; et al. (Исследования и практика в медицине)
Purpose of the study. The aim of this work was to study the effect of conservation in various cryoprotectants on the biomechanical and morphological properties of the umbilical cord (UCA) arteries.Materials and methods. The material for this work was 12 umbilical arteries, which were divided into 4 study groups: (1) native UCA – control without freezing; (2) APC frozen in 5 % dextran with the addition of dimethyl sulfoxide (DMSO) to 10 % and 7.5 % human serum albumin (HSA); (3) APC frozen in glycerin and (4) UCA frozen in propanediol. For all groups, morphological and biomechanical studies were carried out. The statistical data were processed using the GraphPad Prism 9.2.0 program. Analysis of variance was used to find significant differences.Results. Freezing with 5 % dextran, 10 % DMSO and 7.5 % human albumin did not lead to significant changes in the morphology of vascular tissue compared to control. The conserved vascular tissue retains a moderate level of type I collagen, regardless of the method of conservation. The presence of statistically significant differences between the control and frozen UCAs was shown for Young's modulus (p < 0.05; 6.9 [6.8; 7.0] for the native artery; 2.3 [2.0; 2.6] for the artery preserved with the use of dextran, DMSO and human albumin; 2.3 [1.4; 3.2] for the artery preserved in glycerin and 0.8 [0.6; 1.0] – in propanediol, respectively).Conclusion. 1) Freezing and storage of UCA at 5 % dextran, 10 % DMSO and 7.5 % HSA does not lead to a significant change in the morphology of vascular membranes and cell nuclei; 2) The preservation of type I collagen according to the results of IHC is qualitatively reduced from a conditional indicator of +2 to +1 for frozen agroindustrial complexes compared with control ones; 3) Conservation leads to a significant decrease in the modulus of elasticity of the walls of the agroindustrial complex compared with control vessels (p < 0.05).